Animal behavioural genetics - Grandin, Temple (Henry Stewart Talks, 2014)
Nature vs. nurture behaviors – Epigenetics, Innate vs. learned behaviors, Emotional drivers in the brain, The seek/fear switch, Emotional traits have a heritable component, New things are scary and attractive, Different types of fear, Measuring temperament in animals, Animal welfare and genetics, Biological systems overload, An animal is like a country, Future research, Don’t let bad become normal!
Reviewed at 2024/09/17